2011
DOI: 10.1186/1297-9716-42-61
|View full text |Cite
|
Sign up to set email alerts
|

Infection with the gastrointestinal nematode Ostertagia ostertagi in cattle affects mucus biosynthesis in the abomasum

Abstract: The mucus layer in the gastrointestinal (GI) tract is considered to be the first line of defense to the external environment. Alteration in mucus components has been reported to occur during intestinal nematode infection in ruminants, but the role of mucus in response to abomasal parasites remains largely unclear. The aim of the current study was to analyze the effects of an Ostertagia ostertagi infection on the abomasal mucus biosynthesis in cattle. Increased gene expression of MUC1, MUC6 and MUC20 was observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(55 citation statements)
references
References 42 publications
5
48
0
2
Order By: Relevance
“…Strong binding of the mucus to WGA was also reported. 44 As WGA binds to GlcNAc and sialic acid residues, this agreed with the GS-II and MAA binding observed here, which suggested that both residues were present in bovine abomasum mucin.…”
Section: 34supporting
confidence: 76%
See 3 more Smart Citations
“…Strong binding of the mucus to WGA was also reported. 44 As WGA binds to GlcNAc and sialic acid residues, this agreed with the GS-II and MAA binding observed here, which suggested that both residues were present in bovine abomasum mucin.…”
Section: 34supporting
confidence: 76%
“…Mucus from bovine abomasum was reported to bind strongly to the GalNAc-binding lectins, RCA120, DBA, and SBA, 44 which correlated with the binding observed in this study between WFA and SBA and bovine abomasum mucin (sample M57, Figure 3). Strong binding of the mucus to WGA was also reported.…”
Section: 34supporting
confidence: 71%
See 2 more Smart Citations
“…The cattle farming are facing various constraints in Bangladesh and parasitic diseases are the most common among the problems and causes great economic loss to dairy industry by way of retarded growth and low productivity 8,9,10,11 throughout the world due to impacts on economy also 12 and market value of the living animals 13 with a high rate of anthelmintic resistance prevalence 14,15 and increased susceptibility of animals to other infections 16 . The infection causes productivity losses through reduced feed intake and decreased efficiency in feed utilization due to subclinical or chronic infections that are responsible for economic losses 17 . The cattle kept at high level of nutrition and in better management yet declined in their health and productivity, due to their regular infestation with gastrointestinal parasites.…”
Section: Introductionmentioning
confidence: 99%